teaching-learning process of Integral Calculus. analysis of an interactive environment (Revista Electrónica REDINE, 2018)
This research project is part of what I want to develop my doctoral thesis will be framed within the theme of technology and education. The changes in society stem from the rapid progress that has suffered the information and communications technology (ICT) in recent years, which have obviously affected education. These changes require education, training in computer technology, so it should be incorporated as an important part of the curriculum in formal learning. Mathematics plays a major role in the intellectual development of the student, directly affects the mental structures, and where driving the teaching and learning of this, involves creating appropriate scenarios to facilitate the student, the mathematical logical development that the once fits your needs. The research is framed in a quantitative model, therefore I will examine the data numerically oriented, descriptive research. The design used in this research will field since the base ourselves on real facts is necessary to carry out a strategy that allows us to analyze the situation directly at the place where occur, ie, at the headquarters of the Territorial Polytechnic University Andrés Eloy Blanco
Keywords: TIC; teaching and learning; quantitative approach